'Well-kent Faces': Policing Persistent Offenders and the Possibilities for Desistance. (30th October 2018) - Schinkel, Marguerite; Atkinson, Colin; Anderson, Sarah
Abstract: This article focuses on the policing of adult persistent offenders and its implications for desistance. It integrates the findings from two qualitative studies undertaken in Scotland on the experiences of those considered 'persistent offenders' and the police. The article's contribution lies in its close analysis of how adult persistent offenders and the police interact, examining factors before, during and after their encounter. We show that the police's enforcement focus is a significant obstacle to desistance, especially as enacted through intelligence-led policing and the lack of positive discretion towards 'well-kent faces'. However, we also note that frustration with this approach is emerging within Scottish policing and argue for a relatively modest re-orientation of police practice towards a recognition of signals of desistance.